Uji Aktivitas Senyawa Antibakteri Katak Papua (ANTIBACTERIAL ACTIVITY TEST OF PAPUAN FROGS) - Massora, Maria; Kawulur, Elda Irma J. J.; Abubakar, Hermawaty (Jurnal Veteriner, 2018)
Skin and submental glands of Papuan frogs have antibacterial compounds‘ which were capable to impede growth of tested bacteria based on diffusion method. These frogs were Platymantis papuensis , Litoria infrafrenata , Bufo melanostictus , Rana grisea and Rana sp., and the tested bacterial were the positive Gram bacteria ( Staphylococcus aereus , and Bacillus subtilis ) and the negative Gram bacteria ( Escherichia coli and Pseudomonas aeroginosa ). Skin frog which extracted with hot water (100oC) showed antibacterial activity which significantly impeded the growth of tested bacteria using diffusion method.